2007
DOI: 10.1002/pmic.200700543
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics of intracellular Porphyromonas gingivalis

Abstract: Whole-cell quantitative proteomic analyses were conducted to investigate the change from an extracellular to intracellular lifestyle for Porphyromonas gingivalis, a Gram-negative intracellular pathogen associated with periodontal disease. Global protein abundance data for P. gingivalis strain ATCC 33277 internalized for 18 hours within human gingival epithelial cells and controls exposed to gingival cell culture medium were obtained at sufficient coverage to provide strong evidence that these changes are profo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 68 publications
(113 reference statements)
7
92
2
Order By: Relevance
“…Furthermore, P. gingivalis has been demonstrated to invade and survive in host cells, and the presence of FeoB1 would be expected to have deleterious effects on survival of the internalized bacterium. This is consistent with previous observations that demonstrated reduced levels of iron uptake proteins in epithelial cell-internalized bacteria compared with those in extracellular P. gingivalis (20).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, P. gingivalis has been demonstrated to invade and survive in host cells, and the presence of FeoB1 would be expected to have deleterious effects on survival of the internalized bacterium. This is consistent with previous observations that demonstrated reduced levels of iron uptake proteins in epithelial cell-internalized bacteria compared with those in extracellular P. gingivalis (20).…”
Section: Discussionsupporting
confidence: 82%
“…Importantly, iron did not affect feoB1 expression. This contradicts the results of a previous study (20) that attributed the observed downregulation of metal uptake mechanisms in P. gingivalis exposed to host cells to increased iron content of the host cells. Our results demonstrate that the regulation of transcription of P. gingivalis feoB1 is novel compared with the mechanisms of regulation of previously reported feoB1 homologs (2).…”
Section: Discussioncontrasting
confidence: 57%
“…Successful pathogens have developed novel strategies, including bacterially induced epigenetic deregulation that may affect host cell function to facilitate their survival and persistence. Proteomics analyses have significantly contributed toward a deeper understanding of the molecular mechanisms utilized by several oral pathogens such as Streptococcus mutans (30), Streptococcus oralis (31), Fusobacterium nucleatum (32), and P. gingivalis (33)(34)(35) during their interaction with the host. In a previous host-pathogen interaction study performed with epithelial cells, we showed proteome variation in F. alocis with upregulation of many important bacterial proteins (36) that could potentially trigger direct or indirect epigenetic modifications in the host.…”
mentioning
confidence: 99%
“…The adverse effects on the JE may result from the inability of the SerB mutant to penetrate the tissue and thus remain extracellular. Extracellular P. gingivalis organisms are more intensely proteolytic than their intracellular counterparts (63), and protease activity may contribute to apical migration of the JE (20,30). Enhanced PMN infiltration in response to the mutant is likely the direct result of the loss of the SerB enzyme.…”
Section: Discussionmentioning
confidence: 99%